Tumor Budding and Cell Nest Size Are Highly Prognostic in Laryngeal and Hypopharyngeal Squamous Cell Carcinoma: Further Evidence for a Unified Histopathologic Grading System for Squamous Cell Carcinomas of the Upper Aerodigestive Tract. (March 2019) - Boxberg, Melanie; Kuhn, Peer-Hendrik; Reiser, Marianne; Erb, Anna; Steiger, Katja; Pickhard, Anja; Straßen, Ulrich; Koob, Isabelle; Kolk, Andreas; Warth, Arne; Jesinghaus, Moritz; Weichert, Wilko
Abstract : Squamous cell carcinoma (SCC) is the most common cancer of the head and neck region including—among others—laryngeal (LSCC) and hypopharyngeal (HSCC) subsites. LSCC/HSCC are heterogenous diseases with respect to patient outcome. Currently, tumor stage–based patient stratification is essential to predict prognosis and thus selection of the appropriate treatment modalities. In contrast, the prognostic impact of the current HSCC/LSCC grading system according to the WHO classification is limited. Recently, a novel grading system based on tumor budding activity (BA) and cell nest size (CNS) has been introduced for SCC in different anatomic regions of the upper aerodigestive tract. To test and transvalidate this grading scheme in LSCC and HSCC, we retrospectively correlated BA, CNS, and additional histomorphologic parameters with clinicopathologic data of 157 treatment-naive patients. In doing so, we demonstrate that a 3-tiered novel grading system (well-differentiated [nG1], intermediately [nG2], and poorly differentiated [nG3]) based on a sum score for BA and CNS is highly and independently prognostic for patient survival in LSCC/HSCC, strongly outperforming the current WHO grading scheme with a hazard ratio for disease-specific survival of 6.6 for nG2 and 13.4 for nG3 cases ( P <0.001). This finding contributes to a growing body of evidence that a CNS and BA-based pan-entity grading system in SCC might be useful and seems to capture differences in underlying SCC biology crucial for survival. Abstract : Supplemental Digital Content is available in the text.